Community‐based monitoring of wild felid hunting in Central Amazonia. (29th July 2022) - Valsecchi, J.; Monteiro, M. C. M.; Alvarenga, G. C.; Lemos, L. P.; Ramalho, E. E.
Abstract: Hunting is a critical issue in wild felid conservation, contributing to the decline of these species worldwide. Here, we present 18 years of a community‐based monitoring program, quantifying and characterizing wild felid hunting in two sustainable development reserves in Central Amazonia. We investigated how felid hunting was affected by the flood pulse and whether local human population size, habitat type, and total hunting events influenced felid hunting. We recorded 71 adult felids being killed, most of them in opportunistic events (88.7%), usually during hunting expeditions aimed at other game species. Four felid species were recorded in the hunts ( Panthera onca, Leopardus pardalis, Puma concolor, and Leopardus wiedii ) with jaguars accounting for almost half of all hunting events ( N = 35). We found that more felid hunting events occurred during the flooded season, in more populated communities, and in várzea habitats. Most felids were hunted opportunistically, demonstrating the complexity of human‐felid interactions. Stories of attacks on humans are widespread in the study area, which may strengthen an instinctive fear of felids, driving their persecution. The increase of hunting events during the flooded season seems to be related to a higher probability of encounters between humans and wild felids. High waters make fishing difficult, therefore, locals hunt more, entering deep into the forest through flooded habitats. Since jaguars have an arboreal lifestyle during the flooded season in várzea forests, they are easily spotted by locals and have less of a chance to escape since they are slower and more exposed when swimming, which increases the probability of being killed. It is generally acknowledged that involving local stakeholders in conservation projects is essential for their success. In our case, collaboration among researchers and community members was fundamental to access hunting information. We show that community‐based monitoring empowers the local communities and facilitates data collection on sensitive topics. Abstract : We present 18 years of a community‐based monitoring program, quantifying and characterizing wild felid hunting in two sustainable development reserves in Central Amazonia. We recorded 71 adult felids being killed, from four species ( Panthera onca, Leopardus pardalis, Puma concolor and Leopardus wiedii ) with jaguars representing almost half of all hunting events (N = 35). Most of the feline hunting events occurred with the use of shotguns, in highly populated communities during the flood season of várzea habitats.